Pengaruh Tenaga Kerja dan Investasi Aset UMKM terhadap Pertumbuhan Ekonomi Provinsi Jambi - Andre Bowo Sirait (Science of Management and Students Research Journal (SMS), 2022)
economic development is a series of efforts and policies aimed at improving people’s living standart,expanding employment opportunities,equalizing and incrasing people’s incomes,improving regional relations,and through shifting the structure of economic activity from the primary sector to the secondary sector.development also includes changes in the rate of economic growth,reduring income inequlity and eradicating poverty.This study uses secondary data obtainedfrom several agencies and services related to the research titlr.This study also uses multiple linear regression research methods,classical assumption test,coefficient of determination and F test and t test.The results of the regressionequation obtained from research are Y=8,022+0,318X1+0,096X2.With an R square value of 0,533 or 53,3%.This shows that’s the economics growth of jambi province can br explained by 53,3% by the independent variables,namely he UMKM sector and UMKM workforce.The results also show that investment in assets and labor similtanneosly has a significant effect on economic growth in Jambi province.Based on the research conducted,the follow-up action that can be taken by the government is to encourage investment into Jambi Province to be more evenly distributed and implement policies that are able to boost investment so that it is more well realized.